1999
DOI: 10.1016/s1010-7940(99)00026-3
|View full text |Cite
|
Sign up to set email alerts
|

Time trend in the surgical management of patients with lung carcinoma1

Abstract: Over the last two decades, the shift in histological distribution was associated with an increasing proportion of patients with stage I disease, a lower operative mortality and a better 5-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
7
2
Order By: Relevance
“…In the current series, the exploratory thoracotomy and pneumonectomy rates among elderly patients were higher than the rates reported by other authors [7]. This finding can be explained by the time length of the current study and the higher incidence of exploratory thoracotomy and pneumonectomy 20 yrs ago [16].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the current series, the exploratory thoracotomy and pneumonectomy rates among elderly patients were higher than the rates reported by other authors [7]. This finding can be explained by the time length of the current study and the higher incidence of exploratory thoracotomy and pneumonectomy 20 yrs ago [16].…”
Section: Discussioncontrasting
confidence: 63%
“…This finding probably resulted from the changing patterns of lung cancer histology over the last 20 yrs. In a previous analysis which included the same group of patients operated on between 1977 and 1996, it was reported that the proportion of females increased from 12% to 33% and that of adenocarcinoma from 20% to 35% [16]. Changing patterns in the female smoking habit have been proposed as a possible explanation for this epidemiological shift [16±18].…”
Section: Discussionmentioning
confidence: 99%
“…In the current series, the exploratory thoracotomy and pneumonectomy rates among elderly patients were higher than the rates reported by other authors [7]. This finding can be explained by the time length of the current study and the higher incidence of exploratory thoracotomy and pneumonectomy 20 yrs ago [16].…”
Section: Discussioncontrasting
confidence: 63%
“…What has been called BAC represents 2 to 5% of all lung carcinoma (LC), 9,16 -20 although some have suggested that the incidence is increasing. [5][6][7] Surveillance, Epidemiology, and End Results data from 1979 -1998 show a slight increase, but remaining below 4% of all U.S. LC. 8 BAC may show some real increase in Japan, in particular, with more use of low-dose HRCT screening, because the majority of LCs so discovered are BAC or Noguchi type C. 10 -13…”
Section: Epidemiology Incidencementioning
confidence: 99%
“…Some have suggested that BAC is increasing, [5][6][7] although in most recent studies this has not been seen. 8,9 Compared with other types of NSCLC, patients in this spectrum often have a lesser or nonsmoking history, female preponderance, different etiologic and racial factors, a wider range of clinical presentations, less frequent nodal and extrathoracic spread, and usually a more indolent course and favorable prognosis.…”
mentioning
confidence: 93%